Fire, fragmentation, and windstorms: A recipe for tropical forest degradation - Silvério, Divino V.; Brando, Paulo M.; Bustamante, Mercedes M. C.; Putz, Francis E.; Marra, Daniel Magnabosco; Levick, Shaun R.; Trumbore, Susan E. (The Journal of ecology, 2019)
1. Widespread degradation of tropical forests is caused by a variety of disturbances that interact in ways that are not well understood. 2. To explore potential synergies between edge effects, fire and windstorm damage as causes of Amazonian forest degradation, we quantified vegetation responses to a 30-min, high-intensity windstorm that in 2012, swept through a large-scale fire experiment that borders an agricultural field. Our pre- and postwindstorm measurements include tree mortality rates and modes of death, above-ground biomass, and airborne LiDAR-based estimates of tree heights and canopy disturbance (i.e., number and size of gaps). The experimental area in the southeastern Amazonia includes three 50-ha plots established in 2004 that were unbumed (Control), burned annually (Blyr), or burned at 3-year intervals (B3yr). 3. The windstorm caused greater damage to trees (>10 cm DBH) in the burned plots (B1yr: 13 ± 9% of 785 trees; B3yr 17 ± 13% of 433) than in the Control plot (8 ± 4% of 2,300; ± CI). It substantially reduced vegetation height by 14% in B1yr, 20% in B3yr and 12% in the Control plots, while it reduced above-ground biomass by 18% of 77.7 Mg/ha (B1yr), 31% of 56.6 (B3yr), and 15% of 120 (Control). Tree damage was greatest near the agricultural field edge in all three plots, especially among large trees and in B3yr. Trunk snapping (70%) and uprooting (20%) were the most common modes of tree damage and mortality, with the height of trunk failure on the burned plots often corresponding with the height of historical fire scars. Of the windstorm-damaged trees, 80% (B1yr), 90% and s57% (Control) were dead 4 years later. Trees that had crown damage experienced the least mortality (22%-60%), followed by those that were snapped (55%-94%) and uprooted (88%-94%). 4. Synthesis. We demonstrate the synergistic effects of three kinds of disturbances on a tropical forest. Our results show that the effects of windstorms are exacerbated by prior degradation by fire and fragmentation. We highlight that understorey fires can produce long-lasting effects on tropical forests not only by directly killing trees but also by increasing tree vulnerability to wind damage due to fire scars and a more open canopy.